The structure of tertiary education, training and research potential influencing factors - Lőrincz, Mónika; Köpeczi-Bócz, Tamás (Acta Agraria Debreceniensis, 2016)
Nowadays more and more pronounced demand for tertiary education appears as an output of the labor market and the real labor market needs coordination of intention. A necessary condition for the long-term sector strategies, conscious coordination. In Hungary – the sector management level – headed tertiary education training structure and the transformation of the institutional network. There is a close relationship between training supply and research and development potential, as an institution typically the same disciplinary education and research base continues. Based on this, we assume that the structure of the training may influence the development of the restructuring of the research and development potential as well. The institutional network reorganization (merger, liquidation, establishment of new institutions) is expected to result in a former spatial structure of tertiary education in the modification, which in itself is a training and research supply spatial rearrangement may apply. Against this background, questions have been raised as to how the objectives in the current tertiary education strategy for economic operators serving the needs of each territorial unit, how the institution fits into network transformation of economic structure and labor market needs of the regions. In order for the Hungarian tertiary education can meet the requirement for industry standards, an essential part of the structure of industries, and the changes occurring in the economic structure, trends and industry relations in the investigation. On the other hand, we do not ignore those factors are not, which have a determining influence on the tertiary education institutions in training and R&D supply. As part of this study in tertiary education institutions will be examined possible factors influencing education, research and development demand and supply, which gets a prominent role in the economic structure of relations between the territorial dimension in the evolution of discount factors and the nature of particular sectors.